Determining the location of the arsenal in an effort to increase the carrying capacity of marine forces in the critical area of the North Natuna sea - nugraha, Kornia adhi; W, Budisantoso; Astika, I Made Jiwa; Sutrisno, Sutrisno (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2024)
Strategic environmental dynamics in the North Natuna Sea area raises potential threat spots to the territory of the Republic of Indonesia where the Indonesian Navy needs to determine a maritime security strategy where one of the things that must be prepared is the distribution of logistics in the form of ammunition and weapons through development warehouse Arsenal. Through this research, an alternative strategic location was determined as an Arsenal warehouse as a storage place for ammunition supplies used to support the KRI carrying out operational tasks. Alternative construction locations for Arsenal are Lanal Bintan, Lanal Ranai, Lanal Bangka Belitung and Lantamal IV Pontianak. Based on Perkasal No. 17 of 2008 The criteria used and the absolute requirements for determining the location are security, transportation access and supporting facilities. Data collection for this research was carried out using the method of distributing questionnaires and conducting interviews expert. The Delphi method was used in this research to determine and agree on relevant and valid criteria and sub-criteria to be researched at the next stage. Next Method Analytic Network Process (ANP) is used to determine the best alternative with pdata processing process uses Software Super Decision. Then the structure of complex cause and effect relationships is visualized using a matrix and images using the method Decision Making Trial And Evaluation Laboratory (DEMATEL). The results of this research show that the priority of the alternative Arsenal warehouse location is Lanal Bintan with a weight value of 0.536308. Security criteria and sub-criteria for being safe from enemy attacks are the most dominant criteria in determining Arsenal warehouse location decisions.